INDONESIAN CONSUMER KNOWLEDGE MANAGEMENT OF FURADA HAJJ PRODUCTS: A NETNOGRAPHIC STUDY ON THE FACEBOOK PLATFORM - Selly Novita Sari; Kurnia Muhajarah (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
This study aims to explore netizens' knowledge regarding the Furada Hajj product, a type of non-quota Hajj characterized by limited information and uncertain serives guarantees. Using a qualitative approach, the data are presented descriptively. The method used is netnography, where the researcher analyzes natural discussions among Facebook users. This study draws on 260 comments from 64 Facebook posts discussing Furada Hajj, spanning from 2019 to December 2024. The findings show that knowledge about the identity of Furada Hajj dominates, with 168 comments addressing this topic, while satisfaction was the least discussed topic, with only 23 comments. The limited availability of information did not hinder netizens from seeking more detailed information about Furada Hajj. These digital discussions indicate that knowledge—ranging from product, purchasing, to usage knowledge—originates from various sources. This diversity enriches the discussions with multiple perspectives. The study is expected to contribute to efforts in regulating the dissemination of information about Furada Hajj on media platforms to ensure alignment with prevailing regulations